PENGARUH PENGGUNAAN MODEL PEMBELAJARAN EXPLICIT INSTRUCTION TERHADAP HASIL BELAJAR KETERAMPILAN MENULIS KARANGAN NARASI PADA MURID KELAS IV SD NEGERI BONTOMAERO II KECAMATAN BAJENG KABUPATEN GOWA - Rajab, Hikma; Akhir, Muhammad; Akbar, Amal (Bestari: Jurnal Pengabdian Kepada Masyarakat, 2025)
ABSTRACTThis study aims to determine the effect of using the Explicit Instruction model on the learning outcomes of narrative writing skills in grade IV students of SD Negeri Bontomaero II, Bajeng District, Gowa Regency. This type of research is a pre-experimental design and the research design used is one group pretest-posttest design, which is a study carried out with measurements before the pretest and after the posttest. The sample in this study was grade IV with a total of 17 students, 7 male students and 10 female students. The data collection techniques used were the initial test (pretest), treatment (treatment), and final test (posttest). The results of this study indicate that the average score before being given treatment was 52.35% and after being given treatment it became 77.94% with the results of the hypothesis test showing a tcount ˃ ttable value of 9.022 ˃ 2.12. Thus, the hypothesis proposed in the study reads "There is an effect of using the Explicit Instruction learning model on the learning outcomes of narrative writing skills." is declared accepted. This means that the use of the Explicit Instruction learning model has an effect on the learning outcomes of narrative writing skills in grade IV students of Bontomaero II Elementary School, Bajeng District, Gowa Regency.Keywords: Learning Outcomes, Writing Skills, Explicit Instruction Learning Model ABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh penggunaan model Explicit Instruction terhadap hasil belajar keterampilan menulis karangan narasi pada siswa kelas IV SD Negeri Bontomaero II Kecamatan Bajeng Kabupaten Gowa. Jenis penelitian ini adalah pre-experimental design dan desain penelitian yang digunakan adalah one group pretest-posttest design, yaitu suatu penelitian yang dilaksanakan dengan pengukuran sebelum pretest dan sesudah posttest. Sampel pada penelitian ini adalah kelas IV dengan jumlah 17 siswa, 7 siswa laki-laki dan 10 siswa perempuan. Teknik pengumpulan data yang digunakan adalah tes awal (pretest), perlakuan (treatment), dan tes akhir (posttest). Hasil penelitian ini menunjukkan bahwa skor rata-rata sebelum diberi perlakuan adalah 52,35% dan setelah diberi perlakuan menjadi 77,94% dengan hasil uji hipotesis menunjukkan nilai thitung ˃ ttabel yaitu 9,022 ˃ 2,12.